A heterozygous, intragenic deletion of CNOT2 recapitulates the phenotype of 12q15 deletion syndrome. Issue 8 (30th May 2019) - Alesi, Viola; Loddo, Sara; Calì, Federica; Orlando, Valeria; Genovese, Silvia; Ferretti, Daniele; Calacci, Chiara; Calvieri, Giusy; Falasca, Roberto; Ulgheri, Lucia; Drago, Fabrizio; Dallapiccola, Bruno; et al.
Abstract: Only a few individuals with 12q15 deletion have been described, presenting with a disorder characterized by learning disability, developmental delay, nasal speech, and hypothyroidism. The smallest region of overlap for this syndrome was included in a genomic segment spanning CNOT2, KCNMB4, and PTPRB genes. We report on an additional patient harboring a 12q15 microdeletion encompassing only part of CNOT2 gene, presenting with a spectrum of clinical features overlapping the 12q15 deletion syndrome phenotype. We propose CNOT2 as the phenocritical gene for 12q15 deletion syndrome and its haploinsufficiency being associated with an autosomal dominant disorder, presenting with developmental delay, hypotonia, feeding problems, learning difficulties, nasal speech, skeletal anomalies, and facial dysmorphisms.